A UHV standard with option to be used as partial pressure standard. (25th March 2020) - Meng, Dong; Wenjun, Sun; Chengyao, Wu; Lian, Chen; Yali, Li; Meiru, Guo; Lan, Zhao; Dong, Ding; Donghua, Sun; Zhengyi, Ren; Yafang, Ma; Yongjun, Cheng
Abstract: Partial pressure measurement has become indispensable for many applications and contributes to the complete characterization of a vacuum system. In this work, an ultrahigh vacuum (UHV) standard was established for calibrating partial pressure analyzers as a partial pressure standard, and a new method was introduced to generate standard partial pressures, which was named 'the dynamic expansion method based on static expansion vacuum standard injection mode'. The method can produce standard partial pressures in the range from 10 –5 Pa to 10 –10 Pa. The relative standard uncertainty budgets of generated partial pressures ( k = 1) were in the range from 2.8% up to 5.0% from 10 –5 Pa to 10 –9 Pa for nitrogen. Employing this method, the sensitivity calibrations of quadrupole mass spectrometry (QMS) were performed in the partial pressure range of 8.62 × 10 −5 Pa to 1.51 × 10 −10 Pa with single inert He, Ar, and Kr gas in secondary electron multiplier (SEM) mode. Similarly, the calibrations were carried out using active gases (H2, CH4, N2, O2, and CO2 ) in the range 8.56 × 10 −5 Pa to 1.50 × 10 −9 Pa. Additionally, the SEM gains were calibrated for these high-purity gases, on the basis of SEM gain coefficients. QMS sensitivities equivalent to Faraday cup mode were attained, and it was found that the results were approximately consistent with those of previous studies. The data were also in agreement with our theoretical calculation values excluding CH4 .